Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8116387 ZenodoArchiveConcept: 8116386 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8116387 10.53832/edtechhub.0172 2339240:V4SEB3GI 2405685:V8CZHW5B 2405685:ZY6RMGAF
Keywords: _r:AddedByZotZen

Understanding Barriers to Girls’ Access and Use of EdTech in Kenya During Covid-19 - Tembey, Lara; Baier, Jasmin; Ogolla, Concilia; Mohan, Prithika (EdTech Hub and Busara Center for Behavioural Economics, 2021)
The Covid-19 pandemic resulted in the closure of approximately 90,000 schools across Kenya, causing over 18 million pre-primary, primary, and secondary school learners to be out of school throughout 2020. These lockdown measures of Covid-19 are expected to amplify gender inequalities in education and girls’ access to school, with girls likely to have experienced losses in learning during the pandemic to a greater extent than their male counterparts (⇡Malala Fund, 2020). To enable continued learning during this period, numerous education technology (EdTech) solutions and products have been developed to enable remote learning. This technology can be a powerful tool for girls. Studies have shown that girls engage more than boys when provided with the same level of access to technology, and receive more benefits beyond the realm of formal education such as an increase in access to economic opportunities and a greater ability to make informed decisions about their own health (⇡Webb et al., 2020). However, social inequalities, norms and technological constraints can disproportionately prevent girls from accessing and benefiting from EdTech (⇡Crompton et al., 2021). As such, EdTech interventions and products need to be designed and implemented prioritising gender considerations, otherwise they risk increasing the digital gender divide both in terms of access and use of digital technologies and the internet and the development of skills needed to use digital technologies (⇡Kuroda et al., 2019). Our qualitative and quantitative research looked at how access and usage of learning content and edutainment through smartphone and low-tech (such as radio, Interactive Voice Response, TV) EdTech solutions can be optimised to ensure inclusivity of girls, in particular, focusing on the caregiver as the gatekeeper for access to EdTech resources. In terms of access, our research found that caregivers are primarily concerned about financial resources, books and tutors, and often do not consider using EdTech to access educational resources when they are looking for support for their children. Further, our research showed that digital literacy, caregiver involvement, norms about technology for education, and intention are the most promising levers to improve access and use of educational material. An output of the EdTech Hub, https://edtechhub.org
10.5281/zenodo.5524805 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.5524805 10.53832/edtechhub.0048 2339240:5D6SMESW 2339240:7NDUJC6J 2339240:M8IZH5DT 2339240:SIZUDNKL 2339240:XAXIKZJX 2339240:YPDDA6JD 2405685:45G9SKWR 2405685:5ENZ6TFU 2405685:EJ4PXU4S 2405685:JZM7W6QE 2405685:LCHJ5D5W 2405685:RUAJ8C8M
Keywords: _r:AddedByZotZen

Exploring the Gender Differences in Technology Use for Educational Purposes at Home Among Students in Pakistan - Raza, Oneir; Hennessy, Sara (EdTech Hub, 2025)
This report examines gender disparities in the use of educational technology (EdTech) among students in Pakistan, with the aim of informing policies that foster more inclusive and equitable digital learning environments. Drawing on data from a survey of over 2,000 teachers and interviews with EdTech stakeholders in Islamabad, the report explores how sociocultural norms and parental attitudes shape differential access to and use of EdTech at home—particularly disadvantaging female students. It identifies key barriers including limited access to affordable internet and devices, low digital literacy among parents (especially mothers), and prevailing gender norms that restrict girls’ engagement with technology. The findings highlight an urgent need for targeted interventions that address both infrastructural and sociocultural challenges. Recommendations include: expanding subsidised internet and device access in underserved areas; launching community-based digital literacy programmes for parents; creating safe online spaces for female students; promoting positive gender representation in media; and organising inclusive EdTech initiatives to increase girls’ participation. By tackling these barriers through coordinated action, the report offers a roadmap to bridge the gender gap in EdTech adoption and enhance educational equity in Pakistan. Keywords: EdTech; gender; Pakistan; girls’ education; developing economies; educational technology An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14973585 ZenodoArchiveConcept: 14973584 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1057 10.53832/edtechhub.1099
Keywords: _r:AddedByMyEducationEvidence

EdTech That Reaches Marginalised Learners: Relevant Examples for the Indonesian Context - Rui, Yang (Tingting); Upadhyay, Arjun (EdTech Hub, 2022)
This curated list of resources presents a sample of education technology programmes that effectively reach marginalised learners, including children with SEND, girls, and children in frontier, outermost, and disadvantaged regions. This list provides short summaries of lessons in using EdTech such as radio, television, and mobile phones to reach marginalised learners, emphasising interventions and evidence relevant to the Indonesian context. Keywords: marginalised learners, Indonesia, radio, television, mobile phones, girls, no-tech options An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6924683 10.53832/edtechhub.0102 2339240:LDWT8LYC 2405685:JPXVGB3A 2405685:MNMTIMGA 2405685:Q9J54HFA
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
previousshortDOI: 10/ghgng8 previousDOI: 10.5281/zenodo.3874247 EdTechHub.Source: 2405685:VX7UW757 EdTechHub.Source: <this> 2339240:KPL424XH shortDOI: 10/ghgng8 KerkoCite.ItemAlsoKnownAs: 10.5281/ZENODO.3874247 10.5281/zenodo.3874247 10.53832/edtechhub.0025 10/ghgng8 2129771:LBII97HZ 2339240:2R8Z34D2 2339240:FT2TLP7Q 2339240:G93JLKST 2339240:J7DSQVEZ 2339240:QSKUJUNV 2339240:YK2KWXPL 2405685:2D6GK36K 2405685:48AAKD33 2405685:7VFMN2XM 2405685:G7ZB68PJ 2405685:I5WKHBZI 2405685:TP5CQYPQ 2405685:VX7UW757 2405685:YEVYTSJA 2405685:ZUDWQVKI
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7074857 ZenodoArchiveConcept: 7074856 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6326179 10.5281/zenodo.7074857 10.53832/edtechhub.0114 2405685:K5BJUBRE 2405685:REW8F5TJ 2405685:U6G7C62D
Keywords: _r:AddedByZotZen

EdTech for Learners With Cognitive and Learning Disabilities: A Rapid Evidence Review for the Southeast Asian Region - Mitchell, Joel; Thang, Sarah; Zhao, Annette; Hinks, Jessica; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D’Rozario, Jonny; Afzal, Nimra (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with cognitive and learning disabilities. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. We discuss the nature of EdTech for learners living with cognitive and learning disabilities, the effectiveness of these initiatives, and barriers for accessing EdTech. The RER aims neither to advocate nor discourage the use of technology to support education for learners with coginitive and learning disabilities, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; cognitive disabilities; learning disabilities; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10987889 ZenodoArchiveConcept: 10987888 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1006 10.53832/edtechhub.1023 2339240:U7UE5PIN 2405685:B422KBGQ 2405685:HD58IXI3 2405685:PGRMI8NH
Keywords: _r:AddedByMyEducationEvidence; ⛔ No INSPIRE recid found

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14617103 ZenodoArchiveConcept: 14617102 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1084 2339240:C2Z83FSW 2405685:ALBBNZDZ 2405685:BIUPGP3C
Keywords: _r:AddedByMyEducationEvidence

EdTech for Learners With Hearing and Visual Impairments: A Rapid Evidence Review for the Southeast Asian Region - Zhao, Annette; Hinks, Jessica; Thang, Sarah; Mitchell, Joel; Rabi, Asma; Ullah, Noor; Zazai, Rozina; Emerusenge, Aime Parfait; Barnes, Katrina; D'Rozario, Jonny (EdTech Hub, 2024)
This publication is one part of a series of Rapid Evidence Reviews (RERs) that has been produced by EdTech Hub as part of the ASEAN-UK Supporting the Advancement of Girls’ Education (SAGE) Programme. The programme aims to enhance foundational learning opportunities for all by breaking down barriers that hinder the educational achievements of girls and marginalised learners. The purpose of the RERs is to provide education decision-makers with accessible, evidence-based summaries of good practice in specific areas of EdTech in the Southeast Asian region. They are focused on topics which are particularly relevant to marginalised learners, and how to improve their access to education with technology. All the RERs are available at https://edtechhub.org/. This Rapid Evidence Review (RER) provides an overview of existing literature on the use of educational technology (EdTech) for the education of learners with special educational needs and disabilities (SEND) in the Southeast Asian region, specifically those with hearing and visual impairments. It summarises how EdTech is currently being used with these learners, explores how effective these implementations are, and highlights the benefits and challenges of EdTech in this context. The following countries are included in the review’s scope: Brunei, Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand, Timor-Leste, and Vietnam. The RER aims neither to advocate nor discourage the use of technology to support education forlearners with hearing and visual impairments, but rather to provide an accessible summary of existing evidence on the topic so that educators, policymakers and donors might make informed decisions about the potential role of technology in delivering education for learners with SEND. Keywords: SEND; RER; visual impairments; hearing impairments; EdTech; Southeast Asia An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 11197419 ZenodoArchiveConcept: 11197418 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1027 10.53832/edtechhub.1028 2405685:DQ9GNC3J 2405685:M6A4ZHJ3
Keywords: _r:AddedByMyEducationEvidence

EdTech for Marginalised Learners in Southeast Asia: Perspectives from funders and providers on priorities, design, investment, and scaling considerations - Jayasinghe, Neema; Chrisani, Aprillia; Honda, Delanie; Gunawan, Clarissa Jazzlyne (EdTech Hub, 2025)
This report presents the findings of a landscape analysis of EdTech interventions designed for the Southeast Asian context. The analysis aims to understand the extent to which EdTech providers and funders in Southeast Asia address the needs of marginalised learners through their priorities in design, investment, and scaling decisions. It focuses on initiatives targeting marginalised groups and those with potential to scale. The research for the study included interviews with funders engaged in the Southeast Asian EdTech space to examine their perspective on EdTech’s impact on marginalised learners, the approaches they adopt to support inclusive solutions, and the drivers behind their investment decisions. This builds on EdTech Hub’s research for the ASEAN-UK SAGE programme, particularly on how EdTech could be used to support improvements in foundational literacy and numeracy, out-of-school children and youth, and learners with disabilities, as well as overcoming gender barriers to employment through the use of EdTech solutions. An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 15387632 ZenodoArchiveConcept: 15387631 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1117 2405685:SB7G3I83
Keywords: _r:AddedByMyEducationEvidence

Remote Supervision Options for School Quality Assurance Officers: Recommendations for a cost-effective and rapid develop-and-test process - Beoku-Betts, Iman; Ampofo, Rudolph; Haßler, Björn (EdTech Hub, 2024)
The Sierra Leone Secondary Education Improvement Programme II (SSEIP II) is a five-year programme funded by the UK Foreign, Commonwealth and Development Office (FCDO) to support the Ministry of Basic and Senior Secondary Education (MBSSE) to improve learning outcomes for students at secondary level and to increase the enrolment, retention and well-being of girls and children with disabilities in school. Part of the programme includes exploring the use of different digital tools for School Quality Assurance Officers (SQAOs), including tools for remote visits. In December 2022, the EdTech Hub collaborated with the Government of Sierra Leone and implementing partners of the Leh Wi Lan programme (continued under SSEIP II) to better understand what factors affect the variability in the activity levels of SQAOs and the level of engagement with digital tools by school principals. Based on the findings of this research, the SSEIP II project will look at supporting the MBSSE to formalise remote supervision options for the SQAOs, particularly for those with remote clusters. As part of this work, this report focuses on recommendations for how SQAOs can conduct remote school visits, particularly for schools in hard-to-reach areas.An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 10354009 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1002 ZenodoArchiveConcept: 10354008
Keywords: _r:AddedByMyEducationEvidence

EdTech Innovation for COVID-19: Insights from our global call for ideas - Plaut, Daniel; Carter, Alice; Dixon, Miranda; Salami, Taiye (EdTech Hub, 2020)
ZenodoArchiveID: 4768571 previousDOI: 10.5281/zenodo.4277895 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4277895 10.5281/zenodo.4768571 2339240:5M4KPPAH 2339240:MQLLLDAJ 2405685:S7JARBXV 2405685:T2HBLDU6 2405685:TE7A3D6X
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Library Catalog: edtechhub.org Section: general KerkoCite.ItemAlsoKnownAs: 2339240:35E4A2TD 2339240:4LGNB3A8 2339240:AA5FSXJC 2339240:RYJUP2SP 2405685:ATRDA7GD 2405685:BYEPNBQB 2405685:CLFVRHB5 2405685:EIZKB3Q4 2405685:QCXEVZTI 2405685:VMYU87NN 2405685:WWNJCJVG 2405685:ZFJGNIZJ 4656463:7UTAZK7R
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Raising Readers: Can mobile technology enable Kenyan schools to improve parent and carer engagement in reading with their children? - Nicolai, Susan; Khan, Amina; Kartha, Ashwati; Bapna, Akanksha; Kamninga, Tony (EdTech Hub, 2023)
Deploying design-based, mixed-methods research, the study Raising Readers (Phase 1) explores how technology can be best used to strengthen parent and carer engagement with children’s reading in Kenya. In close collaboration with Worldreader, a digital reading organisation, five co-designed modalities (parental training, feedback loops, nudges/messaging, incentives, and reading celebrations) were tested in 14 schools across Nairobi and Kiambu counties over 12 weeks in 2022. The intervention helped to assess the potential of the different modalities in facilitating parental/carer engagement around children’s reading using the BookSmart app. As measured by average reading time, intervention groups showed higher engagement using BookSmart than the control group. ‘Incentives’ led with 39 hours 29 minutes average reading time per school over 12 weeks, followed by ‘reading celebrations’ with 24 hours 13 minutes. ‘Feedback loops’ and ‘training’ had comparable levels (10 hours, 28 minutes, and 9 hours, 27 minutes per school, respectively). ‘Messaging / nudges’ had the lowest engagement (5 hours 57 minutes versus 3 hours 2 minutes in the control group). Parental/carer knowledge, attitudes, and practices supporting their child's reading improved with the interventions. Findings of Phase 1 were used to inform the design of Phase 2. Keywords: Education, app, reading, school, child, Kenya An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8208265 ZenodoArchiveConcept: 8208264 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8208265 10.53832/edtechhub.0057 10.53832/edtechhub.0173 2405685:47KMRR48 2405685:N2E79MUD
Keywords: _r:AddedByZotZen

Rapid Evidence Review on Remote Teaching and Learning - Pacitto, Julia; Hayat, Amal; Hinks, Jessica; Emerusenge, Aime Parfait; Ullah, Noor; Rabi, Asma (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to teaching practices and pedagogies for emergency remote learning. The main aim of this review is to provide education decision-makers, funders, and implementers (among others) with a clear understanding of the available global evidence on effective practices in teaching when students are educated remotely during emergencies, and to assess the relevance of this evidence for low- and middle-income contexts. The findings of the RER are organised by the following five themes: (i) instructional design for remote learning in emergency contexts; (ii) student engagement and interactivity in emergency remote teaching; (iii) assessment, feedback, and pedagogical adaptation in remote teaching during emergencies; (iv) well-being, ‘Maslow before Bloom’, and pedagogies of care in emergency remote teaching; (v) teacher training and support in remote teaching during crises. It also identifies critical gaps in the literature on emergency remote teaching and learning, and suggest avenues for future productive research to address these gaps. Keywords: Education in Emergencies, remote learning, pedagogy, teaching methods, EdTech, emergency remote teaching An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 14967648 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1098 ZenodoArchiveConcept: 14967647
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Summarised Findings from the EdTech Hub Helpdesk - Chuang, Rachel; Moss Coflan, Caitlin (EdTech Hub, 2020)
As of December 2020, EdTech Hub’s Helpdesk has been active for nine months, responding to over 60 requests supporting decision-making on education technology. This document summarises our responses to six commonly asked questions across the topics of reaching marginalised learners, supporting teachers, and using EdTech to mitigate learning loss.
previousDOI: ​10.5281/zenodo.4299931 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4299931 10.5281/zenodo.4768560 2339240:CYPLQHH4 2405685:C49UMTX2 2405685:CWRFU9K9
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:image; _r:CopiedFromEvLib; _zenodoETH; _zenodoETH:submitted

Zero-Rating Educational Content in Low- and Middle-Income Countries - McBurnie, Chris; Adam, Taskeen; Kaye, Thomas; Haßler, Björn (EdTech Hub, 2020)
ZenodoArchiveID: 3784940 previousshortDOI: 10/gg7sqj previousshortDOI: 10/gg7sqj previousDOI: 10.5281/zenodo.3784940 previousshortDOI: 10/gg7sqj EdTechHub.Copy: 2129771:4W3D35BT EdTechHub.Copy: 2129771:4W3D35BT shortDOI: 10/gg7sqj KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3784940 10.53832/edtechhub.0004 10/gg7sqj 2129771:4W3D35BT 2339240:7VJMDZGM 2339240:RSJNXIC6 2405685:DX5RMV6U 2405685:F4PCMTZB
Keywords: F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Learning Continuity in Response to Climate Emergencies: Preliminary insights on supporting learning continuity following the 2022 Pakistan floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Kaye, Tom; Perry, Freya (EdTech Hub, 2022)
This resource is based on preliminary insights from EdTech Hub’s emerging study of Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders to identify feasible ways of using EdTech in response to Pakistan’s 2022 floods. The design adopted for this resource balances generating primary insights from flood-affected parents and teachers quickly and complementing these with insights from the existing evidence base on education in emergencies globally and nationally. EdTech Hub’s study of learning continuity in response to climate emergencies is ongoing. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7326483 ZenodoArchiveConcept: 7326482 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7326483 10.53832/edtechhub.0134 2339240:JZC2BLQQ 2405685:FKCF86HV 2405685:IHTU7JRT 2405685:UXWWBVVX
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Learning Continuity in Response to Climate Emergencies: Pakistan's 2022 floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Radford, Kate; Kaye, Tom; Perry, Freya (EdTech Hub, 2023)
Building on EdTech Hub's preliminary insights, this extended resource explores Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders in identifying scalable and feasible ways of using EdTech in response to Pakistan’s 2022 floods and improving learning responses in future climate emergencies. We identified these approaches by interviewing flood-affected parents and teachers, government education officers, development partners, local NGOs, and international experts in education in emergencies. We find that during the different phases of response to the emergency, communities’ needs and infrastructural realities keep changing. However, existing responses to support learning have not been able to address these needs at scale. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7334016 ZenodoArchiveConcept: 7334015 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7334016 10.5281/zenodo.7716210 10.53832/edtechhub.0135 2339240:JDMXQUFN 2405685:42XI4RCK 2405685:EQ454TF3 2405685:QEMBQCJ6 2405685:ZXRRJ5S6
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

EdTech and Covid-19: Insights from our Sandbox Portfolio. In Collaboration with Sandbox Partner Organisations - Rahman, Asad; Plaut, Daniel; Salami, Taiye; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4776960 2339240:JASYN9AV 2339240:URJVJP9H 2405685:7QBDH9I4 2405685:MXMPWAA2
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Randomised Controlled Trial Protocol: Digital personalised learning to improve literacy and numeracy outcomes in Kenyan classrooms - Major, Louis; Daltry, Rebecca; Otieno, Mary; Otieno, Kevin; Zhao, Annette; Hinks, Jessica; Sun, Chen; Friedburg, Aidan (EdTech Hub, 2023)
This protocol provides a detailed overview of a cluster-randomised controlled trial (RCT) being undertaken in pre-primary schools in Kenya. The RCT seeks to rigorously investigate the impact of a classroom-integrated digital personalised learning (DPL) tool on early grade numeracy and literacy learning outcomes. The protocol is being disseminated prior to endline data analysis to promote transparency and a comprehensive understanding of the RCT approach and design. This protocol was originally published in October 2023. This is an updated version where we have a) clarified that the sample size stated in Sections 2 and 2.2 is the 'pre-attrition' sample; and b) added a paragraph to Section 2.4.1 to provide further clarification regarding the use of code-switching. No changes to the analytical approach have been made. Keywords: digital personalised learning; DPL; Randomised controlled trial; RCT; research methodology; learning outcomes; Kenya An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8354887 ZenodoArchiveConcept: 8354886 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8354887 10.53832/edtechhub.0176 2405685:JNH4277Z
Keywords: _r:AddedByZotZen

Teacher Continuous Professional Development in Tanzania: Lessons Learnt - Chachage, Kristeen; Thakrar, Jay (EdTech Hub, 2023)
This report shares the experience and learning from the activities carried out as part of the Government of Tanzania's efforts to operationalise its National Framework for Teacher Continuous Professional Development (TCPD), which shifts TCPD from discreet workshops to cost-effective, ongoing, school-based professional development. It is among the first of its kind at a national level, particularly in low- and middle-income country contexts. Through a collaborative and responsive approach of adaptive technical assistance and innovation, the EdTech Hub team supported Government of Tanzania partners in developing and implementing a technology-enhanced, school-based, national TCPD system. This report begins with an overview of the activities implemented and then consolidates reflection through nine lessons learnt that could help inform current and future thinking on the design, delivery, and funding of TCPD programming in Tanzania. The TCPD reflected in this report is specific to Tanzania's teaching and learning environment. While we recognise that environments can vary widely, even between countries with similar goals and objectives, the report also seeks to contribute to any current and future analyses that collate features of effective TCPD from around the world. Keywords: teacher professional development; teacher training; technology; learning management system; communities of learning; teacher needs assessment; An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7677950 ZenodoArchiveConcept: 7677949 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7677950 10.53832/edtechhub.0157 2339240:RBNTBT7Z 2405685:9WBV8KPN 2405685:EGL4QHDZ
Keywords: _r:AddedByZotZen

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
previousDOI: 10.5281/zenodo.3958080 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3958080 10.5281/zenodo.5651111 2339240:3DJBGPQM 2339240:AWK2HEZ5 2405685:IJGQTHH9 2405685:UMZVQ4TV 2405685:ZEDSYPGH
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

Minoritised Languages, Education, and Technology: Current practices and future directions in low- and middle-income countries - Zhao, Annette; Mitchell, Joel; Gasanabandi, Gentille; Ullah, Noor; Barnes, Katrina; Koomar, Saalim (EdTech Hub, 2024)
This article explores the current status and future directions of mother-tongue-based multilingual education (MTB MLE) and the use of technology in low- and middle-income countries (LMICs), focusing on the use of minoritised mother tongues. An initial literature review of available academic sources in multiple languages reveals a lack of evidence on the use of technology in MTB MLE across different countries, especially multilingual contexts with greater linguistic diversity. To understand the issue in greater detail and to offer recommendations informed by current practice, interviews and a collaborative workshop with four organisations with relevant educational technology (EdTech) initiatives were conducted. The analysis covers facilitating and limiting factors these organisations have encountered, and the potential positive impact on learners and society generally. We conclude by identifying practical, policy, and research priorities for multilingual education and educational technology in general.
ZenodoArchiveID: 7267302 ZenodoArchiveConcept: 7267301 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7267302 10.53832/edtechhub.0127 2339240:V7ARHU93 2405685:GBBGHCBH 2405685:QADQUWU3 2405685:UTTZNZ24
Keywords: _r:AddedByZotZen